Study of tidal current power generation by vertical axis underwater turbine with diffuser in Costal Peninsular Malaysia - Azman, Idris; Azim, Arshad; Shahrani, Anuar; Ahmmad Shukrie, Md Yudin; Rosdi, Hussin (AENSI, 2014)
Tidal water current in Malaysia can be used as a resource to generated electricity by using turbine, however the velocity of water is very low and the installation of diffuser can accelerate the water velocity. This study purpose is to study the effect on velocity when a diffuser is installed in a turbine and the potential power generation of a turbine produce. The study was analyzed by using 2 dimensional computational fluid dynamic (CFD). The simulation was done with the same size of diffuser but different kind of velocity. The velocity range for this study is from 0.3 m/s – 2 m/s. This velocity was selected because is this study the area selected for this installation of turbine is at Pulau Pangkor where the average minimum velocity is around 0.3 m/s and the average maximum velocity is 2 m/s.